Using podcasts to support learners` positive attitude to listening comprehension in TEFL - Božena Horváthová; Katarína Krištofovičová (Educational Role of Language Journal, 2020)
The aim of the article is to find out how the Internet-based resources (podcasts) affect listening comprehension of learners at a lower secondary school level. First, the concept of listening comprehension, listening strategies, approaches, and possible listening problems in English language learning are tackled. Further on, podcasts, their advantages, disadvantages as well as their appropriate use in English classroom is discussed. Based on relevant theories, application of chosen podcasts in the classroom at a lower secondary level through action research was carried out. The application of the action research showed that podcasts integrated in the classes at all listening stages help develop listening comprehension of learners. By designing suitable lesson plans and introducing challenging activities intensive listening in the classroom can be taught in a meaningful and motivating way.